Effect of canagliflozin on serum uric acid in patients with type 2 diabetes mellitus. Issue 4 (15th February 2015) - Davies, M. J.; Trujillo, A.; Vijapurkar, U.; Damaraju, C. V.; Meininger, G.
<x xml:space="preserve">Abstract</x> Hyperuricaemia is associated with an increased risk of gout, kidney stones and cardiovascular disease. The present post hoc analysis of pooled data from four placebo‐controlled phase III studies assessed the effect of canagliflozin, a sodium‐glucose co‐transporter 2 inhibitor, on serum uric acid levels in patients with type 2 diabetes mellitus (T2DM) and in a subset of patients with hyperuricaemia [defined as baseline serum uric acid ≥475 µmol/l (∼8 mg/dl)]. At week 26, canagliflozin 100 and 300 mg were associated with a ∼13% reduction in serum uric acid compared with placebo. In the subset of patients with hyperuricaemia, placebo‐subtracted percent reductions in serum uric acid were similar to those in the overall cohort. More patients in the hyperuricaemic group achieved a serum uric acid level of <360 µmol/l (∼6 mg/dl) with both canagliflozin 100 mg (23.5%) and 300 mg (32.4%) compared with placebo (3.1%). Incidences of gout and kidney stones were low and similar across groups. In conclusion, canagliflozin treatment decreased serum uric acid in patients with T2DM, including those with baseline hyperuricaemia.